2022
DOI: 10.1038/s41598-021-04482-3
|View full text |Cite
|
Sign up to set email alerts
|

Voltage imaging in the olfactory bulb using transgenic mouse lines expressing the genetically encoded voltage indicator ArcLight

Abstract: Genetically encoded voltage indicators (GEVIs) allow optical recordings of membrane potential changes in defined cell populations. Transgenic reporter animals that facilitate precise and repeatable targeting with high expression levels would further the use of GEVIs in the in vivo mammalian brain. However, the literature on developing and applying transgenic mouse lines as vehicles for GEVI expression is limited. Here we report the first in vivo experiments using a transgenic reporter mouse for the GEVI ArcLig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…ArcLight-derived GEVIs convert a voltage-induced conformational change of the protein into an optical signal allowing the visualization of neuronal circuit activity ( Borden et al, 2017 ; Platisa et al, 2022 ). This mechanism involves the movement of the VSD ( Siegel and Isacoff, 1997 ; Dimitrov et al, 2007 ; Villalba-Galea et al, 2009 ), the photophysical properties of the FP domain ( Kang and Baker, 2016 ; Kang et al, 2021 ), the linker region connecting the VSD to the FP ( Jung et al, 2015 ; Lee et al, 2017 ) as well as potential interactions between neighboring GEVIs via the dimerization of the VSD ( Rayaprolu et al, 2018 ; Leong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ArcLight-derived GEVIs convert a voltage-induced conformational change of the protein into an optical signal allowing the visualization of neuronal circuit activity ( Borden et al, 2017 ; Platisa et al, 2022 ). This mechanism involves the movement of the VSD ( Siegel and Isacoff, 1997 ; Dimitrov et al, 2007 ; Villalba-Galea et al, 2009 ), the photophysical properties of the FP domain ( Kang and Baker, 2016 ; Kang et al, 2021 ), the linker region connecting the VSD to the FP ( Jung et al, 2015 ; Lee et al, 2017 ) as well as potential interactions between neighboring GEVIs via the dimerization of the VSD ( Rayaprolu et al, 2018 ; Leong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, few of the studies examining sensory coding in the mouse OB have been carried out using voltage imaging. 63 , 148 , 150 , 165 , 179 In addition to providing a direct readout of changes in membrane potential from genetically defined cell populations, voltage imaging can measure fast changes in neural activity that would be otherwise obscured when measured using slower imaging methods, and in principle, should be able to measure depolarizing and hyperpolarizing signals. Together, these advances may eventually provide clearer insight into fast temporal coding, and the nature of the inhibitory circuits within the OB.…”
Section: Organization and Circuitry Of The Olfactory Bulbmentioning
confidence: 99%
“…For example, multiple studies have shown the utility of genetically encoded indicators in fruit flies, but have, thus far, only been focused on neuronal-related studies [ 167 , 169 , 176 , 177 , 178 ]. In mice, fewer research studies have utilized GEVIs in vivo, and most of these studies focused on neurological research [ 178 , 179 , 180 , 181 , 182 ]. In addition, Xenopus oocytes were used to characterize Arclight, but did not address any developmental biology [ 183 ].…”
Section: Genetically Encoded Tools That Can Be Used For Studying Deve...mentioning
confidence: 99%